Pro SQL Server Administration - Carter, Peter (Apress : Imprint: Apress, 2015)
Pro SQL Server Administration brings SQL Server administration into the modern era with strong coverage of hybrid cloud environments, In-Memory OLTP, and installation on Server Core. This comprehensive guide to SQL Server Administration for today's DBA helps you to administer the new and key areas of SQL Server, including Columnstore indexes and the In-Memory OLTP feature set introduced in 2014. You will also be guided through the administration of traditional areas of SQL Server, including how to secure your instance, monitor and maintain your instance, and to use features such as AlwaysOn to make your instance highly available. Also covered is the use of SQL Server features to scale out read-only workloads. Pro SQL Server Administration is an all-new book taking up-to-date and modern approach that you'll want and need to further your career as a SQL Server database administrator. Extensive coverage of hybrid cloud environments involving Azure SQL Database Detailed discussions on all new, key features, including AlwaysOn and in-memory support Comprehensive coverage of key skills, such as monitoring, maintenance and indexing.